A new species of Goniagnathus Fieber (Hemiptera: Cicadellidae: Deltocephalinae: Goniagnathini) from China - Duan, Yani; Zhang, Yalin (Zootaxa, 2012)
The deltocephaline leafhoppers of the genus Goniagnathus Fieber are common inhabitants of grassland ecosystem in the Palaearctic, Oriental, Afrotropical, and Australian regions. They are robust, squat leafhoppers readily recognized by their short and broad head, fused male subgenital plates, male style with membranous fracture at midlength, connective short and fused with aedeagus.